Electrode Architecture Design to Promote Charge‐Transport Kinetics in High‐Loading and High‐Energy Lithium‐Based Batteries. Issue 10 (8th September 2021) - Ji, Weixiao; Qu, Huainan; Zhang, Xiaoxiao; Zheng, Dong; Qu, Deyang
Abstract: Rechargeable lithium‐ion batteries have built much of our modern society. Developing high‐loading and high‐energy batteries have become an inevitable trend to satisfy the ever‐growing demand of energy consumption. However, issues related to mechanical instability and electrochemical polarization have become more prominent accompanying the increase of electrode thickness. How to establish a robust and rapid charge transport network within the electrode architecture plays a vital role for the mechanical property and the reaction dynamics of thick electrodes. In this review, principles of charge transport mechanism and challenges of thick electrode development are elaborated. Next, recent progress on advanced electrode architecture design focused on structural engineering is summarized. Finally, a transmission line model is proposed as an effective tool to guide the engineering of thick electrodes. Abstract : In pursuit of developing high‐loading and high‐energy lithium‐based batteries, the performance of an electrode with a conventional configuration is often far from acceptable, not limited to mechanical stability, rate, and safety performance. To address those challenges, it is important to design electrode architecture with fast charge transport kinetics and a robust framework through pore engineering and percolation network construction.